Incidence of neoplasias and effectiveness of postoperative surveillance endoscopy for patients with ulcerative colitis: comparison of ileorectal anastomosis and ileal pouch-anal anastomosis. Issue 1 (December 2016) - Ishii, Hiroaki; Hata, Keisuke; Kishikawa, Junko; Anzai, Hiroyuki; Otani, Kensuke; Yasuda, Koji; Nishikawa, Takeshi; Tanaka, Toshiaki; Tanaka, Junichiro; Kiyomatsu, Tomomichi; Kawai, Kazushige; Nozawa, Hiroaki; et al.
Abstract Background The incidence of neoplasia after surgery has not been sufficiently evaluated in patients with ulcerative colitis (UC), particularly in the Japanese population, and it is not clear whether surveillance endoscopy is effective in detecting dysplasia/cancer in the remnant rectum or pouch. The aims of this study were to assess and compare postoperative development of dysplasia/cancer in patients with UC who underwent ileorectal anastomosis (IRA) or ileal pouch-anal anastomosis (IPAA) and to evaluate the effectiveness of postoperative surveillance endoscopy. Methods One hundred twenty patients who received postoperative surveillance endoscopy were retrospectively reviewed for development of dysplasia/cancer in the remnant rectal mucosa or pouch. Results Three hundred seventy-nine endoscopy sessions were conducted for 30 patients after IRA, while 548 pouch endoscopy sessions were conducted for 90 patients after IPAA. In the IRA group, 5 patients developed dysplasia/cancer during postoperative surveillance and in all cases, neoplasia was detected at an early stage. In the IRA group, no patient developed neoplasia within 10 years of diagnosis; the cumulative incidence of neoplasia after disease onset was 7.2, 12.0, and 23.9 % at 15, 20, and 25 years, respectively. In one case after stapled IPAA, dysplasia was found at the ileal pouch; a subsequent 9 endoscopy sessions in 8 years did not detect any dysplasia. Neoplasia was found more frequently during postoperative surveillance in the IRA group than in the IPAA group (p  = .0028). The cumulative incidence of neoplasia after IRA was 3.8, 8.7, and 21.7 % at 10, 15, and 20 years, respectively, and that after IPAA was 1.6 % at 20 years. Conclusions The cumulative incidence of neoplasia after IPAA was minimal. Those who underwent IRA had a greater risk of developing neoplasia than those who underwent IPAA, although postoperative surveillance endoscopy was able to detect dysplasia/cancer at an early stage. IRA can be the surgical procedure of choice only in selected cases in which it would be of benefit to the patient, with more careful surveillance.